Maternal Vulnerabilities and Disparities in Availability of Antenatal Care Content in Kenya: Analysis of KDHS 2008/9 - Ouma, James; Asweto, Collins O. (Science and Education Publishing, 2017)
Background: ANC provides the opportunity to detect and treat anomalies of pregnancy and access to preventive maternal and child healthcare. However, detailed information about the actual quality and content of ANC in practice is scanty, especially in developing countries. We analyzed the pattern and content of antenatal care service in Kenya in order to assess the quality of ANC. Methods: We used data from the 2008/9 KDHS, a nationally representative survey of women aged 15-49 years in Kenya. Proportion was used for description purpose while association was determined by bivariate and multivariate analysis in which odds ratio with a 95% confidence interval values were calculated. Results: About 50.9% of women sought ANC services either in health centers or dispensaries but these lower level health facilities had more content gaps. Multivariate analysis indicated that maternal age, regional residence, urban residence, wealth index, education and the media influenced ANC initiation and at least 4 ANC visits. There was a coverage gap existing in terms of iron-folate supplementation (66.1%), tetanus toxoid (66.5%), presumptive/preventive treatment for malaria with SP (38.7%) and education on pregnancy complication (44.3%). Nearly a third of women missed the screening for complication during pregnancy. Conclusion: Disparities exist in provision of ANC components, by type of facility attended, rural-urban and low versus higher income biases. Consequently vulnerable women attending ANC miss important care including screening for complication during pregnancy and labor. Efforts should be designed to improve on supplies to government health centers and dispensaries. Well stocked outreach village clinics with the requirements of a comprehensive antenatal care resource allocation should be used to eliminate service disparities. Government policy should help to increase media penetration amongst the masses and sensitize mothers on the importance of ANC.
Keywords: antenatal care; health facility; ANC components; Kenya